Ajaran Tarekat dalam Sistem Pendidikan di Pondok Pesantren: Studi Implementasi Ajaran Tarekat Qadiriyah wa Naqsyabandiyah di Pondok Pesantren Al-Madani Semarang - Siti Asiyah (IIQ An Nur Yogyakarta, 2022)
This study discusses the implementation of the teachings of the Tarekat Qadiriyah wa Naqsyabandiyah in the Education System at the Al-Madani Islamic Boarding School, Semarang City. The method used in this research is descriptive qualitative with a phenomenological approach. The results of the study explain that the education and teaching system in the Al-Madani Islamic Boarding School in Semarang City is a classical, non-classical system, students are obliged to live in Islamic boarding schools, and all students are required to implement the teachings of the Qadiriyah wa Naqsyabandiyyah Tarekat. However, the tarekat teachings that are applied to the santri are not implemented as strictly as the procedures imposed by the tarekat followers who have officially taken bai'at. But here the students are more of the practitioners of the Qadiriyyah wa Nasyabandiyyah tarekat.